Bahaya Hewan Liar (Wild Life Hazard) Terhadap Pelayanan Lalu Lintas Penerbangan di Bandar Udara Internasional Hang Nadim Batam - Nevandy Zaky Alfarisi; Sonhaji, Imam (Politeknik Penerbangan Indonesia Curug, 2024)
This research was conducted at Hang Nadim International Airport, Batam, to investigate the handling of wildlife hazards that impact flight operations and safety. The research methodology used was qualitative descriptive. Data collection techniques included documentation study and direct field observations from December 2020 to March 2021. The research findings indicated that the presence of wildlife activities at Hang Nadim International Airport can compromise the safety objectives of Air Traffic Service (ATS). Instances of aircraft experiencing delays during takeoff and landing were identified, along with frequent discoveries of bird carcasses on the runway that could become Foreign Object Debris (FOD), thereby affecting the smooth flow of air traffic. Special attention is required to manage wildlife hazards in order to enhance flight operations and safety at Hang Nadim International Airport. Additionally, effective coordination and structured management systems are needed, including the establishment of a dedicated unit for wildlife prevention, the procurement of bird repellent devices for prevention purposes, surveillance and control of bird disturbances in the vicinity of the airport, regular tree felling and land clearance around the airport to prevent wildlife nesting and foraging, and infrastructure improvements to eliminate potential entry points for wildlife into the manouvering and movement areas.